Method for producing graphite negative electrode material for lithium electronic battery using waste cathode of aluminum electrolysis
Through the process of coarse crushing, grinding, coating, calcining graphitization and multi-stage wind grading of aluminum electrolytic waste cathode, graphitization of lithium electronic battery graphite negative electrode materials are produced, which solves the harmless disposal and resource utilization of waste cathodes, and realizes efficient utilization and excellent performance production of negative electrode materials.
Patent Information
- Application Number
- CN202211689291.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The prior art is difficult to achieve harmless disposal and resource utilization of aluminum electrolytic waste cathodes, resulting in environmental pollution and waste of resources.
By coarsely crushing, grinding, coating, calcining graphitization and multi-stage wind grading of aluminum electrolytic waste cathode carbon blocks, graphitization of aluminum electrolytic waste cathode carbon blocks, different particle sizes of lithium electronic battery graphite negative electrode materials are produced.
The high-quality utilization of aluminum electrolytic waste cathode and spherical graphite tail material was achieved, and the negative electrode materials of lithium-ion battery with excellent performance and high added value were produced, solving the harmless disposal and resource utilization of waste cathodes.
Smart Images

Figure CN115959656B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of comprehensive utilization of solid waste resources from aluminum electrolysis, and in particular to a method for producing graphite negative electrode materials for lithium-ion batteries using waste cathodes from aluminum electrolysis. Background Art
[0002] Waste cathode of electrolytic aluminum is an important component of overhaul slag. Waste cathode carbon blocks are composed of about 65% carbon and about 35% fluoride, and also contain a small amount of silicate and cyanide. The main environmental hazard of waste cathode comes from fluorine. Due to long-term operation in high-temperature environment, the carbon in waste cathode of electrolytic aluminum has been highly graphitized and has a high recycling value. Therefore, while waste cathode is defined as hazardous waste, it also has strong resource value.
[0003] At present, most domestic enterprises adopt landfill or stockpiling methods to dispose of waste cathodes, which cannot achieve harmless disposal and resource utilization of waste cathodes. Sodium fluoride, aluminum fluoride, cryolite and other components in waste cathodes penetrate into the soil with rainwater, seriously harming the environment and causing fluorine pollution; some enterprises also adopt the method of burning, but the secondary pollution caused by fluoride cannot meet the requirements of environmental protection. Electrolytic aluminum enterprises are in urgent need of applicable waste cathode harmless disposal and resource utilization technology.
[0004] Researchers have conducted extensive research on the harmless and resourceful disposal of waste cathodes. The main related technologies include wet harmless treatment, flotation-sulfuric acid combined treatment, rotary kiln pyrolysis, and high-temperature volatilization-graphitization treatment processes. Wet harmless treatment only dissolves the fluoride in the waste cathode and disposes of it harmlessly, which cannot realize the resource utilization of carbon; although the flotation-sulfuric acid combined treatment can collect carbon components and further purify them with sulfuric acid, the technology has a large amount of wastewater disposal and produces some hazardous waste residues, which cannot realize the high-value utilization of carbon components; the rotary kiln pyrometallurgical process burns and removes the carbon components in the waste cathode carbon blocks, and volatilizes some fluorides. The resulting roasting slag is harmlessly landfilled or used in cement and other building materials industries, and the fluorides are returned to the electrolytic aluminum system. This technology has high carbon emissions and cannot realize the resource utilization of carbon. The fluoride volatilization rate is not high, resulting in high fluorine and sodium content in the roasting slag; the high-temperature volatilization-graphitization process adopts a high-temperature one-step separation method to obtain carbon products and fluoride salt products with high carbon content and high graphitization degree, and industrial demonstration has been carried out.
[0005] The current waste cathode disposal process has a low product added value, and has not achieved harmless disposal and resource utilization. Summary of the invention
[0006] The purpose of this application is to provide a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis to solve the above problems.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] A method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, comprising:
[0009] The waste cathode carbon blocks from aluminum electrolysis are roughly crushed and first ground to obtain fine powder, and the fine powder, asphalt, natural graphite pellet tailings and solvent are mixed and coated to obtain a quasi-spherical coated material;
[0010] The spherical coating material is calcined and graphitized, and the cooled material is subjected to a second grinding and multi-stage wind classification to obtain lithium electronic battery graphite negative electrode materials of different particle sizes.
[0011] Preferably, the coarse crushing is carried out by using a two-stage impact crusher, and the particle size of the obtained particles is less than or equal to 50 mm.
[0012] Preferably, during the treatment process of the two-stage impact crusher, the feed particle size of the first stage is less than or equal to 500 mm, and the discharge particle size is less than or equal to 100 mm;
[0013] Preferably, the impact plate and hammer head of the secondary impact crusher are made of magnetic ductile iron.
[0014] Preferably, the first pulverizing is performed by a vertical mill and a wind classifier, and then magnetic separation is performed to remove iron, and the particle size of the obtained fine powder is 5-50 μm.
[0015] Preferably, the solvent comprises solvent oil and / or white oil;
[0016] Preferably, the mass ratio of the micro powder, the asphalt, the natural graphite pelletizing tailings and the solvent is 10:(0.6-1.5):(1-2):(0.2-0.4), preferably 10:1:1.5:0.3;
[0017] Preferably, the solvent oil is No. 260.
[0018] Preferably, the coating temperature is 120°C-250°C, preferably 150°C, and the time is 2-5h;
[0019] Preferably, the coating is carried out using a kneader or reactor with a heating function.
[0020] Preferably, the calcination graphitization temperature is 2400° C.-3000° C., and the time is 8-20 h; preferably 2800° C., and the time is 12 h.
[0021] Preferably, the calcination graphitization is performed using an Acheson furnace or a series graphitization furnace, and the Acheson furnace or the series graphitization furnace has a fume exhaust system.
[0022] Preferably, the second grinding is performed by a vertical mill, and the surfaces of the grinding disc and grinding roller of the vertical mill are hemispherical silicon carbide wear-resistant material.
[0023] Preferably, the separation classification of the multi-stage wind force classification is 3-6 levels, preferably 5 levels.
[0024] Compared with the prior art, the beneficial effects of this application include:
[0025] The present application provides a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis. Graphite negative electrode materials for lithium electronic batteries of different particle sizes are obtained through coarse crushing, first grinding, coating, roasting and graphitization, second grinding and multi-stage wind classification. Waste cathodes from aluminum electrolysis and low-value spherical graphite tailings are used as raw materials to obtain lithium-ion battery negative electrode materials with excellent performance and high added value, thereby achieving high-quality utilization of hazardous waste and spherical graphite tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0027] Figure 1 A schematic diagram of the main structure of the vertical mill provided for this application;
[0028] Figure 2 A schematic side view of the main structure of the vertical mill provided in this application;
[0029] Figure 3 A process flow chart of a method for producing graphite negative electrode materials for lithium-ion batteries using waste cathodes from aluminum electrolysis provided in this application;
[0030] Figure 4 Schematic diagram of the grinding-classification process in the embodiment.
[0031] Reference numerals:
[0032] 1-feed pipe; 2-middle shell; 3-grinding roller; 4-rocker arm; 5-grinding disc; 6-frame; 7-discharge bin; 8-first reducer; 9-hydraulic cylinder; 10-motor; 11-coupling; 12-second reducer; 13-discharge port. DETAILED DESCRIPTION
[0033] As used herein:
[0034] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0035] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0036] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0037] In these examples, parts and percentages are by mass unless otherwise indicated.
[0038] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0039] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0040] A method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, comprising:
[0041] The waste cathode carbon blocks from aluminum electrolysis are roughly crushed and first ground to obtain fine powder, and the fine powder, asphalt, natural graphite pellet tailings and solvent are mixed and coated to obtain a quasi-spherical coated material;
[0042] The spherical coating material is calcined and graphitized, and the cooled material is subjected to a second grinding and multi-stage wind classification to obtain lithium electronic battery graphite negative electrode materials of different particle sizes.
[0043] The purpose of coating to obtain a spherical coating material is to increase the tap density of the final negative electrode material, thereby improving the electrical properties of the negative electrode material.
[0044] The main function of the solvent is to dissolve the asphalt so as to achieve effective coating of the micro powder and natural graphite pelletizing tailings.
[0045] In an optional embodiment, the coarse crushing is carried out using a two-stage impact crusher, and the particle size of the obtained particles is less than or equal to 50 mm.
[0046] In an optional embodiment, during the processing of the two-stage impact crusher, the feed particle size of the first stage is less than or equal to 500 mm, and the discharge particle size is less than or equal to 100 mm; the second stage uses the discharge of the first stage as feed, and the particle size of the discharge particles of the second stage is less than or equal to 50 mm.
[0047] In an optional embodiment, the impact plate and hammer head of the secondary impact crusher are made of magnetic ductile iron.
[0048] The impact plate, hammer head and other parts of the impact crusher that contact the waste cathode are made of cast iron with strong magnetism. The screen mesh and screen surface of the vibrating screen are made of steel plates or steel mesh with strong magnetism. Non-magnetic materials such as stainless steel shall not be used.
[0049] In an optional embodiment, the first pulverizing is performed using a vertical mill and a wind classifier, followed by magnetic separation to remove iron, and the particle size of the obtained fine powder is 5-50 μm.
[0050] Optionally, the particle size of the finally obtained micropowder can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any value between 5 and 50 μm.
[0051] In an optional embodiment, the solvent includes solvent oil and / or white oil;
[0052] In an optional embodiment, the mass ratio of the micro powder, the asphalt, the natural graphite pelletizing tailings and the solvent is 10:(0.6-1.5):(1-2):(0.2-0.4), preferably 10:1:1.5:0.3;
[0053] In an optional embodiment, the solvent oil is No. 260.
[0054] The preferred solvent oil is No. 260, which has the characteristics of low volatile organic matter content, environmental protection, strong solubility and low price.
[0055] Optionally, the mass ratio of the micropowder, the asphalt, the natural graphite pelletizing tailings (Note: natural graphite pelletizing tailings refer to the difficult-to-pelletize material remaining after natural flake graphite pelletizing, with a particle size of less than 5 μm and a fixed carbon content of generally 88% to 95%) and the solvent oil can be any value between 10:0.6:1:0.2, 10:1:1.5:0.3, 10:1.5:2:0.4 or 10:(0.6-1.5):(1-2):(0.2-0.4).
[0056] In an optional embodiment, the coating temperature is 120°C-250°C, preferably 150°C, and the time is 2-5h;
[0057] In an optional embodiment, the coating is performed using a kneader or reactor with a heating function.
[0058] Optionally, the coating temperature may be 120°C, 150°C, 200°C, 250°C or any value between 120°C and 250°C, and the coating time may be 2h, 3h, 4h, 5h or any value between 2-5h.
[0059] In an optional embodiment, the calcination graphitization temperature is 2400° C.-3000° C., and the time is 8-20 h; preferably 2800° C., and the time is 12 h.
[0060] Optionally, the calcination graphitization temperature can be 2400°C, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C or any value between 2400°C and 3000°C, and the time can be 8h, 10h, 12h, 14h, 16h, 18h, 20h or any value between 8-20h.
[0061] In an optional embodiment, the calcination graphitization is performed using an Acheson furnace or a series graphitization furnace, and the Acheson furnace or the series graphitization furnace has a flue gas exhaust system.
[0062] The purpose of modifying and adding a flue gas exhaust system is to allow the high-temperature flue gas containing fluoride salts and silicates in the spent cathode to overflow the graphitization furnace more easily; the flue gas containing fluoride salts and silicates is collected after cooling.
[0063] In an optional embodiment, the second grinding is performed using a vertical mill, and the surfaces of the grinding disc and grinding roller of the vertical mill are hemispherical silicon carbide wear-resistant material.
[0064] This application requires that the roller surface of the vertical mill be made of silicon carbide ceramics, which is different from the vertical mills used for cement raw materials and clinker in the cement industry.
[0065] In an optional embodiment, the separation level of the multi-stage wind force classification is 3-6 levels, preferably 5 levels.
[0066] Wind force is classified into 3 to 6 levels. According to the "Graphite Anode Materials for Lithium-ion Batteries"
[0067] (GB / T24533-2019) standard for producing negative electrode materials of different particle sizes.
[0068] Optionally, the separation classification of the multi-level wind force classification can be any number of levels among 3, 4, 5, and 6.
[0069] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0070] The components of the waste cathode carbon blocks used in the embodiments and comparative examples of the present application are the same, including the following components:
[0071] C: 60 to 80%, F: 5 to 12%, Na: 5 to 15%, Al: 0.5 to 5%, Si: 0.5 to 2%.
[0072] First, the vertical mill used in this application is described. Figure 1 and Figure 2 As shown, the vertical mill includes a feed pipe 1, a middle shell 2, a grinding roller 3, a rocker arm 4, a grinding disc 5, a frame 6, a discharge bin 7, a first reducer 8, a hydraulic cylinder 9, a motor 10, a coupling 11, a second reducer 12, and a discharge port 13.
[0073] Example 1
[0074] like Figure 3 and Figure 4 As shown, this embodiment provides a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, which specifically includes the following steps:
[0075] (1) The first-stage impact crusher adopts PF1315, the feed size can reach 500mm, and the discharge size can be controlled to 100mm; the second-stage impact crusher adopts PF1007, the feed size can be 100mm, and the discharge size can be controlled to 30mm; the material of the impact plate and hammer head is selected from magnetic ductile iron;
[0076] (2) -30mm materials enter the vertical mill with ceramic roller surface. The vertical mill and wind classifier form a closed-circuit system. The product is 5-30μm. The grinding disc and roller surface of the vertical mill are made of silicon carbide ceramics; 5-30μm micro powder is then subjected to strong magnetic iron removal;
[0077] (3) The mass ratio of 5-30 μm micropowder, coal tar pitch, flake graphite ball tailings, and No. 260 solvent oil is 10.0:1.0:1.5:0.3, and the coating reaction is carried out in a reactor at 150°C for 3 hours to form a spherical shape;
[0078] (4) The spherical micropowder is calcined in a special series graphitization furnace for 8 hours at a temperature of 2600°C (the calcination temperature is controlled by power supply), and then cooled naturally;
[0079] (5) The cooled graphite powder is ground using a vertical mill with a hemispherical ceramic roller surface, and a five-stage classification is adopted to obtain four particle sizes of lithium-ion battery negative electrode material products, with particle sizes of D50 = (20 ± 2) μm, D50 = (17 ± 2) μm, D50 = (12 ± 2) μm, and D50 = (10 ± 2) μm, respectively, and the first discharge specific capacitance is ≥ 340 (mA·h) / g.
[0080] Example 2
[0081] This embodiment provides a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, which specifically includes the following steps:
[0082] (1) The first-stage impact crusher adopts PF1315, the feed size can reach 500mm, and the discharge size can be controlled to 100mm; the second-stage impact crusher adopts PF1007, the feed size can be 100mm, and the discharge size can be controlled to 30mm; the material of the impact plate and hammer head is selected from magnetic ductile iron;
[0083] (2) -30mm materials enter the vertical mill with ceramic roller surface. The vertical mill and wind classifier form a closed-circuit system. The product is 5-30μm. The grinding disc and roller surface of the vertical mill are made of silicon carbide ceramics; 5-30μm micro powder is then subjected to strong magnetic iron removal;
[0084] (3) The mass ratio of 5-30 μm micropowder, coal tar pitch, flake graphite ball tailings, and No. 260 solvent oil is 10.0:1.0:1.5:0.3, and the coating reaction is carried out in a reactor at 150°C for 3 hours to form a spherical shape;
[0085] (4) The spherical micropowder is calcined in a special series graphitization furnace for 12 h at a temperature of 2800°C, followed by natural cooling;
[0086] (5) The cooled graphite powder was ground using a vertical mill with a hemispherical ceramic roller surface, and a five-stage classification was adopted to obtain four particle sizes of lithium-ion battery negative electrode material products, with particle sizes of D50 = (22 ± 2) μm, D50 = (18 ± 2) μm, D50 = (14 ± 2) μm, D50 = (11 ± 2) μm, and D50 = (7 ± 2) μm, respectively, and the first discharge specific capacitance was ≥ 350 (mA·h) / g.
[0087] Example 3
[0088] This embodiment provides a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, which specifically includes the following steps:
[0089] (1) The first-stage impact crusher adopts PF1315, the feed size can reach 500mm, and the discharge size can be controlled to 100mm; the second-stage impact crusher adopts PF1007, the feed size can be 100mm, and the discharge size can be controlled to 30mm; the material of the impact plate and hammer head is selected from magnetic ductile iron;
[0090] (2) -30mm materials enter the vertical mill with ceramic roller surface. The vertical mill and wind classifier form a closed-circuit system. The product is 5-30μm. The grinding disc and roller surface of the vertical mill are made of silicon carbide ceramics; 5-30μm micro powder is then subjected to strong magnetic iron removal;
[0091] (3) The mass ratio of 5-30 μm micropowder, coal tar pitch, flake graphite ball tailings, and No. 260 solvent oil is 10:0.9:1.5:0.25, and the coating reaction is carried out in a reactor at 200°C for 4 hours to form a spherical shape;
[0092] (4) The spherical micropowder is calcined in a special series graphitization furnace for 12 h at a temperature of 2800°C, followed by natural cooling;
[0093] (5) The cooled graphite powder was ground using a vertical mill with a hemispherical ceramic roller surface, and a five-stage classification was adopted to obtain four particle sizes of lithium-ion battery negative electrode material products, with particle sizes of D50 = (22 ± 2) μm, D50 = (18 ± 2) μm, D50 = (14 ± 2) μm, D50 = (11 ± 2) μm, and D50 = (7 ± 2) μm, respectively, and the first discharge specific capacitance was ≥ 360 (mA·h) / g.
[0094] Example 4
[0095] This embodiment provides a method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, which specifically includes the following steps:
[0096] (1) The first-stage impact crusher adopts PF1315, the feed size can reach 500mm, and the discharge size can be controlled to 100mm; the second-stage impact crusher adopts PF1007, the feed size can be 100mm, and the discharge size can be controlled to 30mm; the material of the impact plate and hammer head is selected from magnetic ductile iron;
[0097] (2) -30mm materials enter the vertical mill with ceramic roller surface. The vertical mill and wind classifier form a closed-circuit system. The product is 5-30μm. The grinding disc and roller surface of the vertical mill are made of silicon carbide ceramics; 5-30μm micro powder is then subjected to strong magnetic iron removal;
[0098] (3) The mass ratio of 5-30 μm micropowder, coal tar pitch, flake graphite ball tailings, and No. 260 solvent oil is 10:0.9:1.5:0.25, and the coating reaction is carried out in a reactor at 200°C for 4 hours to form a spherical shape;
[0099] (4) The spherical micropowder is calcined in a special series graphitization furnace for 12 h at a temperature of 2800°C, followed by natural cooling;
[0100] (5) The cooled graphite powder is ground using a vertical mill with a hemispherical ceramic roller surface, and a 5-level classification is adopted to obtain 5 kinds of particle sizes of lithium-ion battery negative electrode material products, with particle sizes of D50=(22±2)μm, D50=(19±2)μm, D50=(16±2)μm, D50=(13±2)μm, and D50=(10±2)μm, respectively, and the first discharge specific capacitance is ≥370(mA·h) / g.
[0101] Compared with Example 1 and Example 2, the calcination time of the spherical micropowder in step (4) is increased from 8 h to 12 h, and the calcination temperature is increased from 2600° C. to 2800° C., while other conditions remain unchanged. The first discharge specific capacitance of the negative electrode material finally obtained is increased from 340 (mA·h) / g to 350 (mA·h) / g, indicating that the calcination temperature and calcination time are important factors affecting the storage performance of the negative electrode material of the lithium ion battery.
[0102] Compared with Example 2 and Example 3, the amount of asphalt in step (3) is increased (the corresponding amount of solvent oil is increased), and the coating reaction is carried out in a reactor at 200°C for 4 hours; step (5) is divided into 5 particle sizes, and other conditions remain unchanged. The first discharge specific capacitance of the negative electrode material finally obtained increases from 340 (mA·h) / g to 350 (mA·h) / g, indicating that the amount of asphalt, coating temperature and time are important factors affecting the storage performance of lithium-ion battery negative electrode materials.
[0103] Compared with Example 3 and Example 4, step (5) is divided into 5 particle sizes, and other conditions remain unchanged. The first discharge specific capacitance of the negative electrode material finally obtained increases from 360 (mA·h) / g to 370 (mA·h) / g, indicating that the graded particle size is an important factor affecting the storage performance of the negative electrode material of the lithium ion battery.
[0104] Comparative Example 1
[0105] Compared with Example 3, in step 2 of Comparative Example 1, the material of -30 mm enters the vertical mill with wear-resistant butt-welded roller surface, the vertical mill and the wind classifier form a closed-circuit system, the product is 5-30 μm, the grinding disc of the vertical mill and the roller surface of the grinding roller are made of wear-resistant butt-welded material; the 5-30 μm micro powder is then subjected to strong magnetic iron removal, and the other steps and conditions remain unchanged. The first discharge specific capacitance of the prepared lithium battery negative electrode material is only 320 (mA·h) / g. This shows that the wear-resistant material of the vertical mill is directly related to the first discharge specific capacitance of the lithium battery negative electrode material.
[0106] Comparative Example 2
[0107] Compared with Example 4, in step 3 of Comparative Example 2, the mass ratio of 5-30 μm micropowder to coal tar pitch and No. 260 solvent oil is 10:0.9:0.25, and the coating reaction is carried out in a reactor at 200°C for 4 hours to form a spherical shape. The other steps and conditions remain unchanged, and the first discharge specific capacitance of the prepared lithium battery negative electrode material is only 360 (mA·h) / g. This shows that the tail of flake graphite ball formation is directly related to the first discharge specific capacitance of the lithium battery negative electrode material.
[0108] The advantages of this application are:
[0109] 1. The carbon in the waste cathode of electrolytic aluminum used in this application has a graphene structure. After high-temperature purification and graphitization, the graphite content of the graphene structure increases, the graphene structure is more complete, and the impurity content is reduced to below 0.01%. The energy density is greater than that of artificial graphite negative electrode materials and natural graphite negative electrode materials;
[0110] 2. Based on the characteristics of large size, lubrication, high strength and strong toughness of the waste cathode, this application adopts the process of coarse crushing by impact crusher - magnetic separation - fine crushing by ceramic roller mill - wind classification to obtain fine waste cathode particles, thereby improving the grinding efficiency of the waste cathode;
[0111] 3. This application uses an Acheson furnace with a flue gas volatilization system or a tandem Acheson furnace to purify and graphitize spent cathodes, and the equipment is mature;
[0112] 4. This application adopts conventional negative electrode material coating materials and processes, and uses environmentally friendly solvent oil as a flux for asphalt;
[0113] 5. This application adopts vertical mill and multi-stage wind classification process to achieve a set of processes and multiple products, which improves product yield and production efficiency;
[0114] 6. This application realizes the high-value utilization of waste cathodes (hazardous waste).
[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0116] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for producing graphite negative electrode materials for lithium electronic batteries using waste cathodes from aluminum electrolysis, characterized in that: include: The waste cathode carbon blocks from aluminum electrolysis are coarsely crushed and first ground to obtain fine powder, and the fine powder, asphalt, natural graphite pellet tailings and solvent are mixed for coating to obtain a spherical coating material; the particle size of the fine powder is 5-50 μm; the solvent includes solvent oil and / or white oil; the mass ratio of the fine powder, the asphalt, the natural graphite pellet tailings and the solvent is 10: (0.6-1.5): (1-2): (0.2-0.4); the coating temperature is 120° C.-250° C.; The spherical coating material is calcined and graphitized, and the cooled material is subjected to a second grinding and multi-stage wind classification to obtain lithium electronic battery graphite negative electrode materials of different particle sizes; the temperature of the calcination and graphitization is 2400°C-3000°C, and the time is 8-20h; the second grinding is carried out by a vertical mill, and the surface of the grinding disc and grinding roller of the vertical mill is hemispherical silicon carbide wear-resistant material; the separation grade of the multi-stage wind classification is 3-6 grades.
2. The method according to claim 1, characterized in that The coarse crushing is carried out by a two-stage impact crusher, and the particle size of the obtained particles is less than or equal to 50 mm.
3. The method according to claim 2, characterized in that During the processing of the two-stage impact crusher, the feed particle size of the first stage is less than or equal to 500 mm, and the discharge particle size is less than or equal to 100 mm.
4. The method according to claim 2, characterized in that: The impact plate and hammer head of the two-stage impact crusher are made of magnetic ductile iron.
5. The method according to claim 1, characterized in that The first grinding is carried out by using a vertical mill and a wind classifier, and then magnetic separation is performed to remove iron.
6. The method according to claim 1, characterized in that The mass ratio of the micro powder, the asphalt, the natural graphite pelletizing tailings and the solvent is 10:1:1.5:0.
3.
7. The method according to claim 1, characterized in that The solvent oil is No.
260.
8. The method according to claim 1, characterized in that The coating temperature is 150° C. and the coating time is 2-5 hours.
9. The method according to claim 1, characterized in that: The coating is carried out using a kneading machine or a reaction kettle with a heating function.
10. The method according to claim 1, characterized in that The graphitization calcination temperature is 2800° C. and the time is 12 hours.
11. The method according to claim 1, characterized in that: The calcination graphitization is performed using an Acheson furnace or a series graphitization furnace, and the Acheson furnace or the series graphitization furnace has a flue gas exhaust system.
12. The method according to any one of claims 1 to 11, characterized in that: The separation classification of the multi-stage wind force classification is 5 levels.
Citation Information
Patent Citations
Negative electrode material of lithium ion battery with graphite covered by asphalt and preparation method thereof
CN101582503A
Graphite composite negative electrode material, preparation method thereof and secondary battery
CN115036484A